Safety, Effectiveness and Tolerance of Buprenorphine-Naloxone in the Treatment of Opioid Dependence: Results from a Nationwide Non-Interventional Study in Routine Care - Apelt, S. M.; Scherbaum, N.; Gölz, J.; Backmund, M.; Soyka, M. (Pharmacopsychiatry, 2013)
Buprenorphine is well known in the treatment of opioid dependence. Despite a high safety profile and good tolerance buprenorphine has been subject to misuse and diversion. To reduce misuse the antagonist naloxone was added and the 4:1 combination of buprenorphine-naloxone was launched in Germany in March 2007. On the basis of the results from international clinical trials a non-interventional study was conducted to gather data on safety, effectiveness, retention and acceptability of buprenorphine-naloxone in the treatment of opioid dependent patients in routine care.A nationwide multicentre 12-month prospective, non-interventional, post-marketing, surveillance study was carried out with 12 assessment points in N=384 opioid dependent patients currently in maintenance treatment from N=69 general practitioners, clinics and outpatient clinics in Germany.N=337 data sets were eligible for analysis. The rates of patients with serious and non-serious adverse events were low with 1.2% and 17.5%, respectively. No deaths occurred during the observational period and only one hospitalization was documented. Concomitant drug use decreased for all illicit substances. Mental health and quality of life measured with standardized self-assessment questionnaires improved significantly. The 12-month retention rate was 57.1%. Of the n=181 patients still in treatment at the end of the observation period, 96.7% continued treatment with buprenorphine-naloxone.The findings of the non-interventional study indicate high effectiveness and safety of buprenorphine-naloxone in the treatment of opioid dependence. The medication was well accepted by opioid dependent patients in long-term substitution treatment with substantial reductions of concomitant drug use and measurable improvement in quality of life.
Keywords: buprenorphine-naloxone; dependence treatment; buprenorphine; naloxone; opioids; routine care; safety